1981
DOI: 10.1007/bf00385359
|View full text |Cite
|
Sign up to set email alerts
|

Control of enzyme activities in cotton cotyledons during maturation and germination

Abstract: Cotton (Gossypium hirsutum L.) embryos excised from bolls 38-43 d after anthesis and cultured in vitro for 4 d on a nutrient agar medium containing 3.8 μM abscisic acid (ABA) developed enzyme activity and accumulated insoluble protein, neutral lipid, and dry weight similar to embryos maturing on the plant. Inclusion of ABA in the medium prevented precosious germination and allowed continued increases in catalase, malate dehydrogenase, citrate synthase, aspartate aminotransferase, and β-oxidation enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Ackerson (2) noted an enhanced frequency of precocious germination of soybean embryos with a decline in endogenous ABA concentration to less than 4 gg/g fresh weight, but a reduction in ABA did not always result in germination. Inhibition of precocious germination by exogenous application of 1 ,AM ABA (Table V) is similar to results with other species (4,6,8). The onset of dormancy during Arabidopsis seed development correlated with the presence of embryo controlled ABA but not with maternally controlled ABA or exogenously applied ABA (1 1).…”
Section: Methodssupporting
confidence: 86%
“…Ackerson (2) noted an enhanced frequency of precocious germination of soybean embryos with a decline in endogenous ABA concentration to less than 4 gg/g fresh weight, but a reduction in ABA did not always result in germination. Inhibition of precocious germination by exogenous application of 1 ,AM ABA (Table V) is similar to results with other species (4,6,8). The onset of dormancy during Arabidopsis seed development correlated with the presence of embryo controlled ABA but not with maternally controlled ABA or exogenously applied ABA (1 1).…”
Section: Methodssupporting
confidence: 86%
“…Analysis of viviparous mutants of corn (3,24) and Arabidopsis (17,19) have shown that precocious germination of these embryos is ( 16) and a-amylase in barley (14), but stimulates synthesis of embryospecific proteins in rapeseed (6), rice (25), and wheat (28). Furthermore, ABA appears to play a role in the maturation of cotton embryos since young embryos cultured on ABA acquire a subset of proteins including a battery of enzymes normally appearing late in embryogeny (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…The number of fully functional glyoxysomes and the activity of the glyoxysomal enzymes, catalase (EC 1.1 1.1.6), malate synthase (EC 4.1.3.2), and isocitrate lyase (EC 4.1.3.1), undergo a well-characterized increase and subsequent decline in activity, with peak activity corresponding to the period ofmaximum lipid metabolism (2,5,12,20). This increase is a common feature of all fatty seeds (2,4,7,12,14,18,20). The increase in activity of glyoxysomal enzymes is due to de novo enzyme synthesis and not merely to activation (13,16,19,29).…”
mentioning
confidence: 99%